Stabilizing selection on genomic divergence in a wild fish population - Neff, Bryan D. (National Academy of Sciences, 2004)
Conservation programs use breeding protocols to increase genomic divergence (by mating genetically dissimilar individuals) in an attempt to circumvent population declines resulting from inbreeding depression. However, disruption of either beneficial gene complexes or local genetic adaptations can lead to outbreeding depression, and thus, there should be a reduction in fitness of individuals at either end of the genomic divergence continuum. Although such simultaneous inbreeding and outbreeding depression has been observed in plant populations, it rarely has been demonstrated in animal populations. Here, I use both genetic and phenotypic measures to show that there is stabilizing selection on genomic divergence in a wild population of bluegill sunfish (Lepomis macrochirus). I also show that breeding individuals that exercise mate choice produce offspring that are closer to the optimal level of genomic divergence than random mating alone would predict.